2007
DOI: 10.1080/01485010701569882
|View full text |Cite
|
Sign up to set email alerts
|

Seminal Vesicle Cyst and Ipsilateral Renal Agenesis: Laparoscopic Approach

Abstract: Seminal vesicle cysts with ipsilateral renal agenesis is rare. When the patient is symptomatic, surgical treatment may be necessary. However, the seminal vesicle is difficult to access surgically, and current transurethral or open surgical approaches have inherent shortcomings. The laparoscopic techniques developed in the last decade may overcome the difficulties in the surgical treatment of seminal vesicle pathology. In this study we report a patient diagnosed with left seminal vesicle cyst and ipsilateral re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2009
2009
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 15 publications
0
7
0
2
Order By: Relevance
“…It offers excellent intra-operative access (usually transperitoneal), minimal blood loss and minimal postoperative morbidity (Cherullo et al, 2002;Hariganji et al, 2004;Liatsikos et al, 2004;van Meegen et al, 2006;Moudouni et al, 2006). The risk of complicated injuries to nearby organs such as the bladder, ureter and rectum is greatly decreased by keeping the dissection tightly adherent to the seminal pathway (Han et al, 2007). Patients may be discharged earlier (Han et al, 2007).…”
Section: Cystmentioning
confidence: 97%
See 2 more Smart Citations
“…It offers excellent intra-operative access (usually transperitoneal), minimal blood loss and minimal postoperative morbidity (Cherullo et al, 2002;Hariganji et al, 2004;Liatsikos et al, 2004;van Meegen et al, 2006;Moudouni et al, 2006). The risk of complicated injuries to nearby organs such as the bladder, ureter and rectum is greatly decreased by keeping the dissection tightly adherent to the seminal pathway (Han et al, 2007). Patients may be discharged earlier (Han et al, 2007).…”
Section: Cystmentioning
confidence: 97%
“…The risk of complicated injuries to nearby organs such as the bladder, ureter and rectum is greatly decreased by keeping the dissection tightly adherent to the seminal pathway (Han et al, 2007). Patients may be discharged earlier (Han et al, 2007). Approximately 15 cases of laparoscopic excision of seminal vesicle cysts have been reported until 2007 (Han et al, 2007).…”
Section: Cystmentioning
confidence: 99%
See 1 more Smart Citation
“…However, with the recent advances in minimally invasive surgical techniques, laparoscopic excision might have been considered as an option for surgical treatment, especially if the preoperative diagnosis supports seminal vesicle cyst [7,8]. Theoretically, the prognosis of cystic malformation is good because of the benign nature of the lymphatic anomaly.…”
Section: Discussionmentioning
confidence: 98%
“…In another three articles the drained fluid was analyzed – in one case spermatozoa and in two cases normal sperm cells were found [7, 8, 9]. Other authors reported patients having children in three cases [4, 6, 10]. Only two patients had one child before the operation.…”
Section: Discussionmentioning
confidence: 99%